INVESTIGATION OF ADMIXTURE SEDIMENTATION IN THE HORIZONTAL SETTLER - Kozachyna, V. A. (Science and Transport Progress, 2016)
Purpose.Sedimentation by gravity is the most common and extensively applied treatment process for the removal of solids from water and wastewater and it has been used for over one hundred years. Sedimentation tanks are one of the major parts of a treatment plant especially in purification of turbid flows. Horizontal settlers are mainly used for purification of high quantity of water. In these tanks, the low speed turbid water will flow through the length of the tank and suspended particle have enough time to settle. Finding new and useful methods for calculating and increasing hydraulic efficiency of horizontal settlers is the objective of many theoretical, experimental and numerical studies.But currently used models and methods in Ukraine do not allow taking into account geometrical form and various design features. In this paper the numerical model was developed to evaluate the effectiveness of horizontal settler with modified structure. Methodology. Numerical model is based on: 1) equation of viscous fluid dynamics; 2) mass transfer equation. For numerical simulation the finite difference schemes are used. The numerical calculation is carried out on a rectangular grid. For the formation of the computational domain markers are used. Findings.The model allows obtaining the purification process in the settler with different form and different configuration of baffles. Originality. A new approach to investigate the mass transfer process in horizontal settler was proposed. This approach is based on the developed CFD model. The fluid dynamics model was used for the numerical investigation of flows and waste waters purification. To investigate influence of baffles on settler efficiency physical experiment was carried out. Practical value.The developed model has more capacity than the existing models in Ukraine. The developed model allows computing quickly the efficiency of water purification in settlers. The model is not computationally expensive. Calculation time of one variant of the problem takes few minutes.